Exploration of Factors Influencing E-Trust and E-Loyalty - Rachmat Gunawan; Jaja Suteja; Undang Juju (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Electronic trust (e-trust) and electronic loyalty (e-loyalty) have always been important issues for online businesses. Understanding and awareness of the importance of creating e-trust and e-loyalty among business actors is still low. Analysis of the influencing factors is still minimal, so it cannot improve business performance. The purpose of this research is to comprehensively explore the factors that influence e-trust and e-loyalty, which has never been done before. The method used is library research in reputable journals, using critical analysis techniques. The results of the study found that there are 50 variables that influence e-trust: e-WOM, e-satisfaction, e-service quality, online shopping experience, privacy, security, online storage, website, expected product performance, loyalty, e-CRM, digital skills, internet, computer skills, security software, service features, perceived usefulness, brand image, price, post-sale treatment, merchant integrity, data integrity, assurance, ease of use, e-scape, responsiveness, customization, reputation, perceived familiarity, efficiency, customer service, social influence, deterrence, knowledge & experience, user interface quality, information quality, e-commerce, clear shopping process, reliable payment system, social commerce components, fulfilment/reliability, risk, perceived technology, previous/prior online purchase experience, service quality, system quality, WOM, corporate image, vendor capacity, and personal values. There are 46 variables that influence e-loyalty: e-trust, e-satisfaction, e-service quality, e-value, e-commitment, perceived privacy, perceived security, website quality, user interface design, internet, reliability, customer service & support, convenience, responsiveness, information quality, ease of use, switching barriers, e-recovery, brand image, price, e-CRM; e-WOM, consumer preferences, perceived usefulness, trust, perceived social presence, perceived enjoyment, perceived value, e-marketing, promotion, customer interface quality, service quality, technology trust, customization, interactivity, character, satisfaction, switching costs, cultivation, community, care, choice, e-brand love, web knowledge, innovativeness, and commitment. This research can be used as a guide and reference for researchers, stakeholders, and business actors, and it is hoped that further research can be carried out in other fields.